Does Artificial Intelligence Have an Impact on Monetary Policy Effectiveness in Indonesia? - Anisa Syahidah Mujahidah; Anisa Syahidah Mujahidah (Journal of Central Banking Law and Institutions, 2026)
The study empirically investigates the implications of  AI Readiness, Broad Money, and political stability for monetary policy effectiveness, as measured by a composite index. The study uses robust fixed-effect panel data estimation techniques to analyse data from 19 OIC member countries between 2019 and 2023, with a focus on Indonesia. The results show that AI readiness and political stability have a substantial positive impact on monetary policy effectiveness in Indonesia, whereas Broad Money has a significant adverse impact. These findings offer relevant policy implications for AI transformation in the financial sector, particularly for effective monetary policy. These findings establish a relationship between the quest for high-quality institutions, defined by the readiness of  AI implementation, political stability, and stable broad money. The study adds to a recent body of  literature on the impact of  AI and other variables on the efficiency of  monetary policy.